Nilai Sosial Emosional Anak Usia Dini pada Majalah Sibamas - -, Lutfi Laely Kohariyah (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
SIBAMAS magazine is an early childhood magazine used in learning activities in PAUD, especially banyumas regency. In SIBAMAS magazine there are various indicators with images that can develop the emotional social value of early childhood according to their age. Social emotional values which are to provide knowledge and skills to children through habituation and example. These emotional social values that will later form a positive attitude for children, so that children can adjust to themselves and the community environment. Based on my research, that the emotional social value in SIBAMAS magazine is in accordance with indicators of early childhood emotional social development in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 137 of 2014 on national standards of early childhood education. The scope of social emotional development in it there is the value of self-awareness, a sense of responsibility for oneself and the human being. Keyword: Socially Emotional, Early Childhood, SIBAMAS Magazine